The Influence of L1 in Learning L2; A Case Study of Java-English in Tidar University - Febriana Aminatul Khusna; Sekar Lathifatul Aliyah (Journal of English Language Teaching, Linguistics, and Literature Studies, 2021)
Pronunciation is a significant aspect in communication that associates to how people reveal words for communication. People who speak with the L2 language can be impacted with their L1 in their pronunciation. The accent of L1 tends to dominate L2 in pronouncing a particular word. Thus, it also cannot be easily discharged when someone speaks in L2. This research intends to investigate the impact of L1 in learning L2, especially the Javanese accent, into an English accent. Descriptive qualitative would be utilized as the methodology for constructing this paper. Subsequently, the data would be analyzed using the Comparison and Contrast by Clark (1995) method. Based on the finding, the researchers found 15 words pronounced with Javanese accents. It indicates that L1 can influence pronouncing a word in L2. It will be better if this condition can be conquered. Learning and practicing more are advised in order to retaliate this problem.